2021
DOI: 10.1038/s41436-021-01211-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatic PIK3R1 variation as a cause of vascular malformations and overgrowth

Abstract: Purpose Somatic activating variants in the PI3K-AKT pathway cause vascular malformations with and without overgrowth. We previously reported an individual with capillary and lymphatic malformation harboring a pathogenic somatic variant in PIK3R1, which encodes three PI3K complex regulatory subunits. Here, we investigate PIK3R1 in a large cohort with vascular anomalies and identify an additional 16 individuals with somatic mosaic variants in PIK3R1. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) can be enhanced by CapG, an additional oncogenic signaling mutation that leads to increased PI3K/Akt activation [ 16 18 ]. Somatic PIK3R1 variation can also be attributed to genetic variation in the PI3K-AKT pathway and can induce vascular malformations and overgrowth [ 19 ]. The PI3K δ enzyme complex, including PIK3CD, PIK3R1, or phosphatase and tensin homolog (PTEN), is primarily present in the immune system and comprises a catalytic (p110 δ ) and regulatory (p85 α ) subunit, and both overactivation and underactivation of PI3K δ lead to impaired and dysregulated immunity, for instance, B-cell lymphomas [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) can be enhanced by CapG, an additional oncogenic signaling mutation that leads to increased PI3K/Akt activation [ 16 18 ]. Somatic PIK3R1 variation can also be attributed to genetic variation in the PI3K-AKT pathway and can induce vascular malformations and overgrowth [ 19 ]. The PI3K δ enzyme complex, including PIK3CD, PIK3R1, or phosphatase and tensin homolog (PTEN), is primarily present in the immune system and comprises a catalytic (p110 δ ) and regulatory (p85 α ) subunit, and both overactivation and underactivation of PI3K δ lead to impaired and dysregulated immunity, for instance, B-cell lymphomas [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA template derived from peripheral blood was added to Platinum SuperFi II PCR Master Mix (Invitrogen) along with CBL primers (forward (5′-GGAAACAAGTCTTCACTTTT-3′) and reverse (5′-GCTCAATCTTTACATCCTTATC-3′)) and amplified by PCR as previously described ( Cottrell et al 2021 ). Because of limited residual volume associated with the buccal samples, DNA was incorporated into a 50-µL solution of 1× Platinum SuperFi II PCR Master Mix (Invitrogen) and 20 nM CBL primers in the sample tube for 10 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, products were purified using 1.8× SPRIselect and used as DNA template in a second round of PCR. Amplified products were purified using 1.5× SPRIselect and processed as described ( Miller et al 2020b ; Cottrell et al 2021 ). Sequencing of the pooled libricons (amplicon libraries; Miller et al 2020b ) occurred on an Illumina iSeq 100.…”
Section: Methodsmentioning
confidence: 99%
“…Somatic mutations in PIK3CA, PIK3R1, PIK3R2, AKT1, AKT3, and TEK lead to hyperactivation of the PI3K signaling pathway, which results in abnormal tissue growth, angiogenesis, and lymphangiogenesis. Activating mutations in this pathway have been identified in vascular tumors, vascular malformations, and many disorders associated with tissue overgrowth ( Cottrell et al, 2021 ; Davies et al, 2021 ; Rivière et al, 2012 ).…”
Section: Opportunity To Repurpose Cancer Drugsmentioning
confidence: 99%
“…No drugs have been approved by the U.S. Food and Drug Administration for treatment, and standardized treatment protocols have not been developed. The use of targeted next-generation sequencing (NGS) has demonstrated that many vascular anomalies are caused by mosaic mutations in highly conserved genes that control cell proliferation and survival ( Cottrell et al, 2021 ; Keppler-Noreuil et al, 2014 ; Lindhurst et al, 2011 ; Madsen et al, 2018 ; Mirzaa et al, 2013 ; Siegel et al, 2018 ). This has transformed our fundamental understanding of the pathobiology of vascular anomalies and, for the first time, revealed potential pharmacologic targets for these disorders.…”
Section: Introductionmentioning
confidence: 99%